The Influence Of Capital, Fertilizer Prices And Sharia Financing On The Income Of Oil Palm Farmers (Case Study Of Dolok District, North Padang Lawas Regency) - Hasibuan, Titin Efrida; Anggraini, Tuti; Silalahi, Purnama Ramadani (JURNAL MANAJEMEN MOTIVASI, 2025)
This research aims to analyze the influence of capital, fertilizer prices and sharia financing on the income of oil palm farmers in Dolok District, North Padang Lawas Regency. Farmers' income is influenced by various factors, including the capital used for production, fluctuating fertilizer prices, and access to sharia financing which offers an interest-free alternative in the agricultural financial system. The research method used is quantitative with a multiple linear regression approach. Data was obtained from 35 respondents who are oil palm farmers who are customers of Bank Syariah Indonesia (BSI) KCP Gunung Tua. The research results show that fertilizer prices have a significant effect on the income of oil palm farmers, while capital and sharia financing do not have a significant effect. The simultaneous test (F test) shows that the three independent variables together have a significant influence on the income of oil palm farmers. However, the coefficient of determination (Adjusted R Square) value of 40.4% shows that there are still other factors that influence the income of oil palm farmers in the area